2013
DOI: 10.1186/1471-2156-14-75
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of Phyllomedusa distincta Lutz, 1950 (2n = 2x = 26), P. tetraploidea Pombal and Haddad, 1992 (2n = 4x = 52), and their natural triploid hybrids (2n = 3x = 39) (Anura, Hylidae, Phyllomedusinae)

Abstract: BackgroundNatural polyploidy has played an important role during the speciation and evolution of vertebrates, including anurans, with more than 55 described cases. The species of the Phyllomedusa burmeisteri group are mostly characterized by having 26 chromosomes, but a karyotype with 52 chromosomes was described in P. tetraploidea. This species was found in sintopy with P. distincta in two localities of São Paulo State (Brazil), where triploid animals also occur, as consequence of natural hybridisation. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 42 publications
4
22
0
5
Order By: Relevance
“…Hence, in the specimens of Phyllomedusa distincta examined by Bruschi et al [2014], restricted het-ITSs are located in the heterochromatic centromeric regions of chromosomes 8 and 11, whereas in the individuals studied by Gruber et al [2013], these are found in the centromeric regions of chromosomes 6, 7 and 11 ( table 1 ). However, the possibility that these frogs actually belong to 2 different cryptic species should not be ignored.…”
Section: Large Itss In Restricted Heterochromatic Regions (Restrictedmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in the specimens of Phyllomedusa distincta examined by Bruschi et al [2014], restricted het-ITSs are located in the heterochromatic centromeric regions of chromosomes 8 and 11, whereas in the individuals studied by Gruber et al [2013], these are found in the centromeric regions of chromosomes 6, 7 and 11 ( table 1 ). However, the possibility that these frogs actually belong to 2 different cryptic species should not be ignored.…”
Section: Large Itss In Restricted Heterochromatic Regions (Restrictedmentioning
confidence: 99%
“…An unexpected discovery was made by Gruber et al [2013] in P. tetraploidea . This tetraploid species (4n = 52) probably originated from the closely related diploid P. distincta (2n = 26) or, alternatively, from a common diploid ancestor of both species by autopolyploidy [Pombal and Haddad, 1992;Brunes et al, 2010].…”
Section: Large Itss In Restricted Heterochromatic Regions (Restrictedmentioning
confidence: 99%
“…In other cases, however, hybrids produce calls more similar to those of one of the parental species and sometimes, calls that include unique traits (e.g., in European water frogs of the genus Pelophylax; Wycherley et al 2002b) where call variation also is in line with genome dosage effects in triploid hybrids (Hoffmann & Reyer 2013). An additional example documented here is that of the leaf frogs, Phyllomedusa distincta and P. tetraploidea, which produce triploid hybrids (Haddad et al 1994;Gruber et al 2013). These frogs have very similar calls but subtle differences exist and the hybrids have intermediate number of notes (Fig.…”
Section: Effects Of Hybridizationmentioning
confidence: 99%
“…Comparative spectrograms and oscillograms exemplifying the effect of hybridization on the call structure of anurans. The two tree frogs Phyllomedusa distincta (diploid) and P. tetraploidea (tetraploid) co-occur and hybridize in Ribeirão Branco, south of São Paulo state, Brazil, producing triploid hybrids (3n = 39) (Haddad et al 1994;Gruber et al 2013). Their advertisement calls are of similar structure and indistinguishable to the human ear, but have subtle quantitative differences (Student's t-Test = 11.06; p < 0.0001): 6-11 notes (7.8 ± 1.02; n = 31 calls from 3 males) in P. distincta, 8-17 notes (12.8 ± 2.4; n = 58 calls from 8 males) in P. tetraploidea (4n).…”
Section: Species Identification and Delimitation By Advertisement Callsmentioning
confidence: 99%
“…In the present work our efforts were the use of replication banding after 5-bromodeoxiuridine treatment, an useful approach to identify homeologous chromosomes (Kasahara et al 2003, Silva et al 2004, Gruber et al 2007, Gazoni et al 2012, Gruber et al 2013). This methodology is very effective for comparative analyses in fishes, amphibians, and reptiles due to the difficulty in producing classical Q, G, and R banding patterns in the chromosomes of the ectothermic vertebrates (Sumner 2003).…”
Section: Introductionmentioning
confidence: 99%